When subtle is the most effective. An analysis of product placement effectiveness in multitasking environments - Gunawardena, Thuthi (Auckland University of Technology, 2013)
Product placement is seen by marketers as the proverbial “golden goose,” it can do no wrong and if left alone it will prosper. Unfortunately, this is not true today as the typical consumer has access to a vast array of entertainment options, all of which can be conveniently accessed from home. This viewing environment presents a unique dilemma for marketers because when at home consumers engage in other activities while watching television such as cooking, cleaning and responding to emails. The attempt to complete each activity efficiently activates a consumer’s task-directed behaviour, which will lead to selective attention. This research aims to research is to investigate the role of task-directed behaviour plays in affecting the effectiveness of product placements. Existing literature on multitasking and its effect on television product placement are still in its early development. This study seeks to bridge a gap in current knowledge by conducting an empirical study on the effect of cognitive load and task directed behaviour on the level of brand recall, recognition and behavioural intention within both prominent and subtle placements . The findings of this study indicate decreasing rates of recall, recognition and behavioural intentions for prominent brands more than for subtle brands, when visual tasks are present. It is expected that results would be significant different if unfamiliar brands were used. However, further research is needed to see if result can be replicated.
Keywords: Product placement; Distractor devaluation effect; Subtle placement; Prominent placement; Advertising effectivness